Causes of perinatal death at ramathibodi hospital, Bangkok, Thailand - Yaowalug Boonpasat (2018)
In the group of fetal deaths, the causes are mostly unknown even after complete autopsy.In the group of neonatal deaths, hyaline membrane disease is the major cause, especially in infants weighing 1,001-2,500 gm at birth. In those with birth weights over 2,500 gm, infection, especially of the lungs, was the common cause. These two major causes of death have decreased during the last 3 years of this study (1977-1979). Congenital malformations are also an important cause of death. © 1982 Oxford University Press.